Informisanost logopeda sa područja Crne Gore o asistivnoj tehnologiji za decu sa poremećajima verbalne komunikacije - Arsenić, Ivana; Veljković, Zorica; Vukićević, Anđela (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Assistive technology includes tools and devices that can be used in their original, modified, or adapted form. The use of assistive technology in children with verbal communication disorders enables effective establishment of social interaction, expression of needs and desires, as well as increasing independence, self-esteem, and productivity. Aim. The aim of this research was to assess the level of awareness of speech and language therapists employed in the territory of the Republic of Montenegro about assistive technology for children with verbal communication disorders. Also, the study aimed to determine which sociodemographic variables influence the respondents' estimated level of information. Methods. Forty-eight speech therapists employed in the Republic of Montenegro participated in the research. The research used an online questionnaire that was specifically designed for the purpose of this research. Results. The results showed that the respondents believed that they were informed about assistive technology for children with verbal communication disorders (M = 4.03, SD = 0.46). The analysis of the results showed that the respondents' gender and the length of service were not statistically significantly related to the estimated level of awareness. The obtained data indicate that 27.10% of respondents do not use any device in the treatment of children with verbal communication disorders. The Cboard application is most often used in speech and language treatment. The results showed that speech and language therapists lack knowledge about high-assistive technology, as well as training in its use. Conclusion. The training of speech and language therapists should focus on the application of assistive technology in the treatment of children with verbal communication disorders, developing a team approach and international cooperation, as well as providing information on institutions that offer technological assistance to users.
Keywords: asistivna tehnologija; informisanost; logopedi; verbalna komunikacija